Phytoremediation efficiency of Crinum asiaticum in enclosed spaces based on morphological traits and CO absorption dynamics - KHAMBALI KHAMBALI; ELSIE TANISHA DENANDA; RUSMIATI RUSMIATI; DEMES NURMAYANTI; IVA RUSTANTI ERI WARDOYO; SLAMET WARDOYO (Society for Indonesian Biodiversity, 2025)
Abstract. Khambali, Denanda ET, Rusmiati, Nurmayanti D, Wardoyo IRE, Wardoyo S. 2025. Phytoremediation efficiency of Crinum asiaticum in enclosed spaces based on morphological traits and CO absorption dynamics. Biodiversitas 26: 6205-6211. Indoor air pollution, particularly carbon monoxide (CO), poses a serious health risk in poorly ventilated environments. This study evaluates the phytoremediation potency of Crinum asiaticum, a native ornamental species, in reducing indoor CO concentrations—an area with limited prior investigation. A quasi-experimental design was employed using a 1.2 m × 0.9 m × 0.7 m test chamber, into which CO gas sourced from a 110 cc petrol-powered motorcycle was introduced. Five groups were assessed: one control (no plants) and four treatment groups containing one to four C. asiaticum specimens. CO levels were measured before and 45 minutes after exposure using a calibrated gas detector. Descriptive analysis revealed a dose-dependent reduction in CO levels, with the T4 group achieving the greatest decrease of 28.40%. The T3 and T2 groups treatments reduced concentrations by 14.59% and 7.34%, respectively. The T1 group showed a modest reduction of 4.47%, indicating limited absorption capacity at minimal biomass. The Kruskal-Wallis test indicated significant differences among groups (p<0.001), confirming a positive correlation between plant quantity and CO absorption capacity. Although final CO concentrations remained above national indoor air quality standards, the findings underscore the potential of C. asiaticum as a natural biofilter. Its integration into indoor environments not only supports air remediation but also enhances biodiversity through the use of indigenous phytoremediator species. This study presents a novel, eco-friendly approach to mitigating indoor air pollution and advancing environmental health strategies.